제2철 이온을 이용한 상온조건에서 하수슬러지의 생물전기화학 혐기성소화 성능향상 - 풍경(Qing Feng); 송영채(Young-Chae Song); 장성호(Seong-Ho Jang) (Daehan hwan'gyeong gonghag hoeji, 2016)
The influence of ferric ion ($Fe^{+3}$) on bioelectrochemical anaerobic digestion for sewage sludge was explored at ambient temperature ($25^{°}C$). Before the addition of ferric ion, the removal of volatile solids (VS) was 65.9% and the specific methane production rate was 370 mL/L/d. After the addition of ferric ion (200 ppm) to feed sludge, the bioelectrochemical anaerobic digester was more stable in the state variables including pH, alkalinity, COD and VFAs, and the VS removal and specific methane production rate were increased to 69.8% and 396 mL/L/d, respectively. However, the methane content in biogas was slightly reduced by the addition of ferric ion, indicating that the activity of planktonic anaerobic bacteria (PAB) was more improved after the addition of ferric ion. The dominances of syntrophic bacteria (Cloacamonas) and hyrolytic bacteria (Saprospiraceae, Ottowia pentelensis) in the PAB were increased by the addition of ferric ion. The addition of ferric ion improved the performance of bioelectrochemical anaerobic digestion for sewage sludge at ambient temperature. 상온조건($25^{°}C$)에서 하수슬러지처리를 위한 생물전기화학 혐기성소화조의 성능에 미치는 제2철 이온($Fe^{+3}$)의 영향을 연구하였다. 생물전기화학 혐기성소화조를 상온에서 운전하였을 때 pH, 알카리도, COD 및 VFAs 등의 상태변수들은 안정하였으며, VS 제거율과 비메탄발생율은 각각 65.9% 및 370 mL/L/d이었다. 생물전기화학 혐기성소화조에 제2철 이온(200 ppm)을 주입한 후 상태변수들의 안정도는 더욱 향상되었으며, VS 제거율 및 비메탄발생량은 각각 69.8%, 396 mL/L/d로 증가하였다. 그러나, 제2철 이온을 주입 이후에 바이오가스의 메탄함량은 76.6%로 주입 이전의 77.3%에서 비하여 약간 감소하였다. 부유슬러지의 미생물 군집을 변화를 분석한 결과 공생 혐기성미생물(Cloacamonas) 및 가수분해균(Saprospiraceae, Ottowia pentelensis) 등의 우점균의 비율이 제2철 이온의 주입으로 증가하였다. 이것은 철이온의 주입으로 부유혐기성미생물(planktonic anaerobic bacteria, PAB)의 활성이 증가하였음을 나타낸다. 제2철 이온은 상온조건에서 하수슬러지처리를 위한생물전기화학 혐기성소화조의 성능을 향상시킨다.